2019
DOI: 10.1055/s-0039-1694019
|View full text |Cite
|
Sign up to set email alerts
|

A versão femoral está associada a alterações na força dos músculos do quadril em mulheres com impacto femoroacetabular sintomático?

Abstract: Resumo Objetivo O objetivo deste estudo foi avaliar a associação da anteversão femoral e da força dos músculos do quadril em indivíduos com síndrome do impacto femoroacetabular. Método Os ângulos de versão femoral descritos nas imagens de ressonância magnética articular e os testes isocinéticos foram avaliados retrospectivamente entre julho de 2016 e dezembro de 2017. Os critérios de inclusão foram: a) versão femoral avaliada pelo mesmo radiologista; b) ângulo α ≥ 55°; e c) ausência de dor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…In patients with increased AVA but normal foot progression angle, Passmore et al [25] showed that higher gluteus medius muscle forces are needed for walking with the patient-specific femoral geometry compared to a normal, typical geometry. Several other studies [61][62][63][64] investigated the relationship between femoral geometry and muscle strength. To the best of our knowledge, no studies showed a clear relationship between the femoral geometry (combined AVA and NSA), muscle strength and gait pattern.…”
Section: Plos Onementioning
confidence: 99%
“…In patients with increased AVA but normal foot progression angle, Passmore et al [25] showed that higher gluteus medius muscle forces are needed for walking with the patient-specific femoral geometry compared to a normal, typical geometry. Several other studies [61][62][63][64] investigated the relationship between femoral geometry and muscle strength. To the best of our knowledge, no studies showed a clear relationship between the femoral geometry (combined AVA and NSA), muscle strength and gait pattern.…”
Section: Plos Onementioning
confidence: 99%
“…No previous studies have assessed the relationship between the GTA index and the femoral anteversion angle during clam exercise. In the mid-position of the hip, if the femoral anteversion angle is excessive, the position of the greater trochanter is displaced posteriorly compared to that of the normal anteversion angle [ 62 , 63 ]. When the femoral anteversion angle is increased, the arm length in hip extension and abduction is reduced [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patient with increased AVA but normal foot progression angle, Passmore et al [29] showed that higher gluteus medius muscle forces are needed for walking with the patient-speci c femoral geometry compared to a normal, typical geometry. Several other studies [70][71][72][73] investigated the relationship between femoral geometry and muscle strength. To the best of our knowledge, no studies showed a clear relationship between the femoral geometry (combined AVA and NSA), muscle strength and gait pattern.…”
Section: Discussionmentioning
confidence: 99%